Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1161/01.cir.94.12.3214
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent Atrioventricular Block During Radiofrequency Catheter Ablation

Abstract: Inadvertent atrioventricular block may occur during or late after radiofrequency catheter ablation. It is associated with ablations for (1) anterior and midseptal accessory pathways and atrioventricular nodal reentry and (2) relative institutional inexperience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(59 citation statements)
references
References 23 publications
1
54
0
2
Order By: Relevance
“…Particularly, AV block after RFCA is a serious problem in children especially for septal APs and AVNRT. 10 Schaffer et al 16 reported that an increased risk of inadvertent AV block was associated with a decreased operator experience, and anterior, mid, or right posterior septal AP sites. There was no AV block in our patients with septal APs.…”
Section: Complicationsmentioning
confidence: 99%
“…Particularly, AV block after RFCA is a serious problem in children especially for septal APs and AVNRT. 10 Schaffer et al 16 reported that an increased risk of inadvertent AV block was associated with a decreased operator experience, and anterior, mid, or right posterior septal AP sites. There was no AV block in our patients with septal APs.…”
Section: Complicationsmentioning
confidence: 99%
“…[1][2][3] In a few cases, para-Hisian AP ablation may fail because of limited energy delivery at these sites or other unclear reasons when energy delivery is optimal. 4 The inferior vena cava approach (IVC-A) via a femoral vein has been a dominant approach for ablation of para-Hisian APs, and a few cases of successful para-Hisian AP ablation by the noncoronary cusp approach (NCC-A) or the superior vena cava approach (SVC-A) have been reported. [5][6][7] However, when should para-Hisian APs be mapped and ablated by the NCC-A or SVC-A remains unclear.…”
mentioning
confidence: 99%
“…In addition, we deem that the use of cryoenergy is justified by the lower incidence of AV block compared to AVNRT RF ablation in pediatric population [4][5][32][33][34] , even if a higher recurrence rate is reported. It can be speculated that the detailed 3D EA reconstruction of Koch's triangle combined with the use of cryoenergy may account for the absence of any acute and long-term complications in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…This latter aspect has greater relevance especially in the pediatric population. In this subset of patients anatomic considerations such as a small triangle of Koch with the possible higher risk of AV node damage should be taken into account in AVNRT ablation 5 . Furthermore, the use of fluoroscopy exposes children to the potential harmful effects of radiations [6][7] .…”
Section: Introductionmentioning
confidence: 99%